Comparison of neuroprotective effect of Forsythia suspensa leaf extract and forsythiaside, one of its metabolites. Issue 22 (17th November 2018) - Chen, Liqing; Lin, Lixia; Dong, Zhe; Zhang, Liwei; Du, Huizhi
Abstract: As one of authentic Chinese medicinal materials in Shanxi Province, leaves of Forsythia suspensa (Thunb.) Vahl ( F. suspensa, Lianqiao in Chinese) have been used as alternative for the relief or treatment of inflammation. The study aimed to compare the neuroprotective effects of extract from F. suspensa leaves and forsythiaside against inflammation and apoptosis induced by lipopolysaccharide (LPS) on hippocampal slices. The cultured hippocampal slices were treated with extract (5 and 50 μg/mL) and forsythiaside (5 and 50 μg/mL), respectively, followed by LPS treatment for 24 h. The present study showed that 60% ethanol extract of F. suspensa leaves exhibited better neuroprotective effect than equivalent forsythiaside. Abstract :